1997
DOI: 10.1016/s0166-6851(97)00124-2
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles stephensi salivary glands bear receptors for region I of the circumsporozoite protein of Plasmodium falciparum

Abstract: In the mosquito, Plasmodium sporozoites rupture from oocysts found on the midgut wall, circulate in the hemolymph and invade salivary glands where they wait to be injected into a vertebrate host during a bloodmeal. The mechanisms by which sporozoites specifically attach to and invade salivary glands are not known but evidence suggests that it is a receptor-mediated process. Here we show that the major surface protein of sporozoites, the circumsporozoite protein (CS), binds preferentially to salivary glands whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 23 publications
(23 reference statements)
2
82
0
1
Order By: Relevance
“…5 These flanking regions contain short, highly conserved sequences denoted as Region I (RI) and RII regions, 3 that are the binding domains for glycosaminoglycan heparin sulfate receptors, which are found on the surface of hepatocytes 6 and mosquito salivary glands. 7 The RI and RII domains appear to play important roles in parasite invasion to host cells, both in the mosquito and the vertebrate host. 7,8 The CR of Plasmodium vivax CS protein has been shown to be dimorphic, characterized by tandem repeats of the nonapeptide GDRADGQPA in the VK210 sequence, 5 and ANGAGNQPG that corresponds to the VK247 variant sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 These flanking regions contain short, highly conserved sequences denoted as Region I (RI) and RII regions, 3 that are the binding domains for glycosaminoglycan heparin sulfate receptors, which are found on the surface of hepatocytes 6 and mosquito salivary glands. 7 The RI and RII domains appear to play important roles in parasite invasion to host cells, both in the mosquito and the vertebrate host. 7,8 The CR of Plasmodium vivax CS protein has been shown to be dimorphic, characterized by tandem repeats of the nonapeptide GDRADGQPA in the VK210 sequence, 5 and ANGAGNQPG that corresponds to the VK247 variant sequence.…”
Section: Introductionmentioning
confidence: 99%
“…7 The RI and RII domains appear to play important roles in parasite invasion to host cells, both in the mosquito and the vertebrate host. 7,8 The CR of Plasmodium vivax CS protein has been shown to be dimorphic, characterized by tandem repeats of the nonapeptide GDRADGQPA in the VK210 sequence, 5 and ANGAGNQPG that corresponds to the VK247 variant sequence. 9 Both nonapeptides sequences are repeated ~20 times in their corresponding proteins; however, there is extensive polymorphism with regard to the number of repeats.…”
Section: Introductionmentioning
confidence: 99%
“…Sporozoites are formed in a complex process, termed sporogony, that represents the longest developmental phase of the Plasmodium life cycle [3]. Although sporozoites are likely passively transported throughout the hemocoel, there is evidence that they specifically recognize the salivary glands through a receptor-mediated process [4][5][6][7]. Sporozoites breach the basal lamina and acinar gland cells and accumulate in the salivary duct [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that sporozoite-salivary gland interaction is species specific and receptor mediated; the glands being involved in both recognition and invasion [5]. It is also known that sporozoites only invade the distal parts of median and lateral lobes of female salivary glands and that recombinant circumsporozoite (CS) protein binds specifically to Anopheles stephensi salivary glands, particularly to the median and distal lateral lobes of the gland [6]. Mosquito saliva contains a large number of biomolecules responsible for antihemostatic activity, which assist hematophagous arthropods during the feeding process [7].…”
Section: Introductionmentioning
confidence: 99%